Quantitative analysis of Y-Chromosome gene expression across 36 human tissues - Godfrey, Alexander K.; Naqvi, Sahin; Chmátal, Lukáš; Chick, Joel M.; Mitchell, Richard N.; Gygi, Steven P.; Skaletsky, Helen; Page, David C. (Genome Research, 2020)
Little is known about how human Y-Chromosome gene expression directly contributes to differences between XX (female) and XY (male) individuals in nonreproductive tissues. Here, we analyzed quantitative profiles of Y-Chromosome gene expression across 36 human tissues from hundreds of individuals. Although it is often said that Y-Chromosome genes are lowly expressed outside the testis, we report many instances of elevated Y-Chromosome gene expression in a nonreproductive tissue. A notable example is EIF1AY, which encodes eukaryotic translation initiation factor 1A Y-linked, together with its X-linked homolog EIF1AX. Evolutionary loss of a Y-linked microRNA target site enabled up-regulation of EIF1AY, but not of EIF1AX, in the heart. Consequently, this essential translation initiation factor is nearly twice as abundant in male as in female heart tissue at the protein level. Divergence between the X and Y Chromosomes in regulatory sequence can therefore lead to tissue-specific Y-Chromosome-driven sex biases in expression of critical, dosage-sensitive regulatory genes.